Etnopedagogy in Primary Social Studies Education: A Literature Review on Fostering Students' Creativity - Yuli Budhiarti; Lutma Ranta Allolinggi (Jurnal Pedagogi dan Inovasi Pendidikan, 2026)
Creativity is an essential competency that should be developed through meaningful learning experiences in primary education. However, Social Studies learning is often dominated by teacher-centered instruction, limiting students' opportunities to think creatively and connect learning with their cultural environment. Ethnopedagogy, which integrates local wisdom and cultural values into the learning process, has the potential to create more contextual and engaging learning experiences. This study aims to examine the role of ethnopedagogy in fostering students' creativity in primary Social Studies education through a literature review. Relevant publications from 2018 to 2026 were collected from reputable academic databases and analyzed using content analysis and narrative synthesis. The findings indicate that ethnopedagogy promotes contextual learning by connecting Social Studies content with students' local culture and everyday experiences. This approach encourages inquiry, collaboration, problem-solving, and reflective learning, thereby supporting the development of creativity through fluency, flexibility, originality, and elaboration. In addition, ethnopedagogy strengthens students' cultural awareness and active participation in the learning process. The review concludes that ethnopedagogy provides an effective pedagogical framework for enhancing creativity in primary Social Studies education and recommends its integration into curriculum design and classroom practices. Further empirical studies are needed to validate its effectiveness in different educational contexts